Excellent self-rated health and health behaviors in the United States adolescent population - Kimmel, Katheryne Ann (Kansas State University, 2022)
Background: Adolescence represents a uniquely critical period for establishing health behaviors. As behaviors established in youth tend to track into adulthood, there is opportunity to encourage establishment of positive lifestyle behaviors. However, more research is needed evaluating relationships between lifestyle behaviors and positive health outcomes like well-being, especially in youth populations. Thus, the aim of this study was to examine health behaviors in the United States adolescent population and their association with excellent self-rated health. Methods: The FLASHE study, a cross-sectional survey of parent-adolescent dyads conducted by the National Cancer Institute, provided publicly available data used to examine multiple lifestyle behaviors. Participants in this analysis were adolescents (n=1350, mean age = 14.5) with complete data for exposures (beneficial and detrimental food intake, importance of family meals, typical free time physical activity and sedentary time, trouble sleeping, and meeting sleep guidelines), excellent well-being, and potential confounders. Logistic regression analyses were used to evaluate relationships between individual lifestyle behaviors and excellent well-being. Results: In this sample 47% of males and nearly 35% of females reported excellent self-rated health. After complete statistical adjustment, the following lifestyle variables were statistically significantly associated with excellent self-rated health: beneficial food intake, family meal importance, physical activity levels, and sleep quality. Conclusions: Adolescents engaging in healthy lifestyle behaviors were more likely to report excellent self-rated health. These findings support interventions targeting improvements in lifestyle behaviors.
Keywords: Self-rated health; Health outcomes; Health behaviors; Wellbeing; Cancer prevention